2017
DOI: 10.1002/jmv.24807
|View full text |Cite
|
Sign up to set email alerts
|

Localization of VZV in saliva of zoster patients

Abstract: Varicella zoster virus (VZV) in saliva from six herpes zoster patients and one chickenpox patient was found to be exclusively associated with epithelial cells by confocal microscopy. VZV localization with antibody specific to the VZV glycoprotein E was detected primarily on the membrane but was also inside the cell. Epithelial cells with VZV were still present in saliva in one out of two tested zoster patients after 10 months of recovery. Saliva from healthy controls (non-shingles patients, n = 5) did not show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Despite viremia in four of five animals on 4 dpi, the saliva from only one of the five animals was SVV DNA positive while all buccal samples were negative, suggesting a possible non-hematogenous route for dissemination into the oral mucosa or delay in replication within epithelial cells. Our study demonstrated positive shedding of SVV into the oral cavity of non-human primates, as is also shown in human VZV acute infection of adults (Mehta et al., 2012), patients with zoster (Cohrs et al., 2008, Mehta et al., 2008, 2013, 2017, Depledge et al., 2011, Nagel et al., 2011, Gershon et al., 2015), and patients with zoster sine herpete (Furuta et al., 2001; Gershon et al., 2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Despite viremia in four of five animals on 4 dpi, the saliva from only one of the five animals was SVV DNA positive while all buccal samples were negative, suggesting a possible non-hematogenous route for dissemination into the oral mucosa or delay in replication within epithelial cells. Our study demonstrated positive shedding of SVV into the oral cavity of non-human primates, as is also shown in human VZV acute infection of adults (Mehta et al., 2012), patients with zoster (Cohrs et al., 2008, Mehta et al., 2008, 2013, 2017, Depledge et al., 2011, Nagel et al., 2011, Gershon et al., 2015), and patients with zoster sine herpete (Furuta et al., 2001; Gershon et al., 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Saliva— DNA was extracted from saliva using the QIA-Amp DNA kit (Qiagen; Germantown, MD) (Mehta et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some may question whether saliva VZV DNA detection by using the centrifugated cell pellets of saliva or the concentrated saliva fluid may be useful for early diagnosis. Indeed, the recent study demonstrated that VZV DNA was abundant in the pelleted fraction of saliva because VZV in saliva is cell‐associated . So, further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In space shuttle experiments, spleen and thymic masses were reduced in flight mice [20], and significant changes in thymopoiesis was reported in healthy flight astronauts in association with a defined physiological, emotional, and physical stress event [21]. Immune system dysregulation has now been demonstrated to occur during spaceflight and persist during 6 months orbital spaceflights [17,22,23,24]. These results suggest that immune system aberrations caused by stressors associated with space travel should be included when estimating risk for pathologies such as cancer.…”
Section: Introductionmentioning
confidence: 99%